DEHYDRATION OF EDIBLE MUSHROOMS (PLEUROTUS OSTREATUS) - Salas de la Torre, N. (2003)
The edible mushroom Pleurotus ostreatus have been subjected to thermal, chemical and thermal-chemical treatment. The results show that the chemical treatment produces a more effective enzymatic inactivation compared to the other two treatments. Also, the experimental study of fungi dehydration carried out at 55 ° C reveals that the critical moisture content is 10.4 kg water / kg dry solids, the equilibrium moisture is 0.22 kg water / kg of solid .